A rare localization of a foreign body: breast - Soukaina, Fekkoul; Oussama, Lamzouri; Hafsa, Taheri; Hanane, Saadi; Ahmed, Mimouni (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
We report a case of 52 years old that presented with an intramamary foreign body that was introduced by the patient herself, the foreign body was removed and the sent to Psychiatric Department for follow up. It’s a rare case of foreign body localization that can induce infections and abscess, but our patient was not infected hopefully.